Pengaruh Metode Critical Incident Terhadap Hasil Belajar Bahasa Indonesia Kelas IV SD Negeri 58 Kota Bengkulu - Alhaktullah, Denis (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
This type of research is quantitative with an experimental approach. Data collection techniques use observation, questionnaires and documentation. This research was carried out at SD Negeri 58 in Bengkulu City. The total population was 131 students and the samples taken were 26 students as control and 26 students as experiments. Based on the result of research conducted by researchers regarding the influence of the use of the critical incident method on the learning outcomes of Indonesia language subjects in class IV students at SD Negeri 58 in Bengkulu City, it can be seen from the result of the hypothesis using the F test on two groups with the results obtained Fsig (0,001) < (0,05) and F count= 14.030, which means the working hypothesis in this research is accepted, namely that the learning outcomes of Indonesia language subjects taught using the critical incident method are better than students who do not use the critical incident method at SD Negeri 58 in Bengkulu City. This is proven by the number of posttest Indonesia language learning result in the experimental group which was 1970 higher than the control group 1750.